2018
DOI: 10.1007/s11307-018-1227-6
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Intraoperative Imaging Modalities to Improve Surgical Precision

Abstract: Intraoperative imaging (IOI) is performed to guide delineation and localization of regions of surgical interest. While oncological surgical planning predominantly utilizes x-ray computed tomography (CT), magnetic resonance imaging (MRI), and ultrasound (US), intraoperative guidance mainly remains on surgeon interpretation and pathology for confirmation. Over the past decades however, intraoperative guidance has evolved significantly with the emergence of several novel imaging technologies, including fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 96 publications
0
46
0
1
Order By: Relevance
“…More recently, image guided surgery has generated quite a bit of interest in the field of molecular imaging, with several investigators assessing various contrast agents along with various imaging techniques [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Both preclinical and clinical studies have shown the benefits that image guidance can offer during all sorts of surgical applications.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, image guided surgery has generated quite a bit of interest in the field of molecular imaging, with several investigators assessing various contrast agents along with various imaging techniques [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Both preclinical and clinical studies have shown the benefits that image guidance can offer during all sorts of surgical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Optical fluorescence imaging in combination with drug delivery systems unifies properties that can advance image-guided medicine. These features can be exploited for example to promote early cancer diagnosis based on fluorescence imaging and to enhance the real-time visualization of tumor margins during oncologic surgery [ 1 , 2 ]. Due to their biocompatibility, liposomes which are lipidic nanovesicles that mimic biological membranes are widely used for the delivery of drugs or contrast agents, both in clinical and preclinical setups [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely recognized that intraoperative diagnosis technologies contribute to minimize surgical damage, preserve normal tissue and reduce the rate of recurrence for tumor resection surgery [1][2][3][4][5]. Optical imaging is characterized by low cost, nonionizing radiation and simple and high resolution [6][7][8], which is promising for design of an intraoperative diagnosis instrument.…”
Section: Introductionmentioning
confidence: 99%